The effects of Red Bull Energy Drink compared with caffeine on cycling time-trial performance - Quinlivan, A.; Irwin, C.; Grant, G. D.; Anoopkumar-Dukie, S.; Skinner, T.; Leveritt, M. D.; Desbrow, B. (International Journal of Sports Physiology and Performance, 2015)
This study investigated the ergogenic effects of a commercial energy drink (Red Bull) or an equivalent dose of anhydrous caffeine in comparison with a noncaffeinated control beverage on cycling performance. Eleven trained male cyclists (31.7 ± 5.9 y 82.3 ± 6.1 kg, VO2max = 60.3 ± 7.8 mL/kg·min) participated in a double-blind, placebo-controlled, crossover-design study involving 3 experimental conditions. Participants were randomly administered Red Bull (9.4 mL/kg body mass [BM] containing 3 mg/kg BM caffeine), anhydrous caffeine (3 mg/kg BM given in capsule form), or a placebo 90 min before commencing a time trial equivalent to 1 h cycling at 75% peak power output. Carbohydrate and fluid volumes were matched across all trials. Performance improved by 109 ± 153 s (2.8%, P = .039) after Red Bull compared with placebo and by 120 ± 172 s (3.1%, P = .043) after caffeine compared with placebo. No significant difference (P > .05) in performance time was detected between Red Bull and caffeine treatments. There was no significant difference (P > .05) in mean heart rate or rating of perceived exertion among the 3 treatments. This study demonstrated that a moderate dose of caffeine consumed as either Red Bull or in anhydrous form enhanced cycling time-trial performance. The ergogenic benefits of Red Bull energy drink are therefore most likely due to the effects of caffeine, with the other ingredients not likely to offer additional benefit.